Kompetensi Pedagogik Guru, Pendidikan Agama Islam Dalam Keluarga Dan Motivasi Belajar Tehadap Hasil Belajar Siswa - Abdul Malik; Munzir Hitami; Zamsiswaya Zamsiswaya (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to determine the effect of the pedagogic competence of Islamic Religious Education teachers, religious education in the family, learning motivation, on the learning outcomes of Islamic Religious Education students at Pekanbaru State Senior High School. This research method uses survey research with a quantitative approach. The research was conducted at SMAN 1 Pekanbaru City, SMAN 9 Pekanbaru City and SMAN 11 Pekanbaru City. The sample of this research was 115 respondents from a total population of 1,010 students. Data analysis used a simple linear regression test and multiple linear regression with the results: There is a significant effect of 46.4% on the pedagogic competence of PAI teachers, Religious Education in the Family and Learning Motivation simultaneously on the learning outcomes of PAI students at SMAN Pekanbaru City. This means that the higher the level of PAI Teacher Pedagogic Competence, Family Religious Education, and Learning Motivation, the better the PAI Learning Outcomes of Students at Pekanbaru State Senior High School. While there are 53.6% who are influenced by other variables not examined in this study such as learning discipline, the role of school principals, teacher professionalism, learning models, learning methods, digital-based teaching materials, digital-based learning media, learning facilities, learning resources, environment other social and non-social.Â Keywords:Â  Pedagogic Competence, Religious Education in the Family, Learning Motivation, Learning Outcomes